Pengaruh Kompetensi Sumber Daya Manusia Dan Komunikasi Interpersonal Terhadap Efektivitas Kerja - Rika Endah Budiharti; Kokom Komariah; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine how much influence the competence of human resouces, interpersonal communication has on work effectiveness for employees of PT.Agronesia Saripetejo, Sukabumi City. Responden in this study were 35 people who were shown to employees of PT.Agronesia Saripetojo Sukabumi,City. This research method uses quatitative methods with an associative descriptive approach. In this study, the Normality Test, Simultaneous Statistical Test ( F Test ) and Partial Statistical Test ( T Test ) were carried out. The results in this study indicate that there is a simultaneous positive influence between human resouce competence, interpersonal communication and work effectiveness with a result of 12,639 > 3,292, which means that the calculated F value is greater than the F table. Partially human resouce competence has a positive but not significant effect on work effectiveness, this is evidenced by the value obtained from the result of T count > T table (2,579 > 2,032) with a significance value of (0,015 > 0,05). Interpersonal communication has a positive and significant effect on work effectiveness, this us evidenced by the calculated T value which is greater than T table (3,511 > 2,032) with a significance of 0,001 < 0,05. Keywords : Human Resource Competence, Interpersonal Communication, Work Effectiveness